Peran Balai Pemasyarakatan dalam Proses Rehabilitasi dan Reintegrasi Anak yang Berhadapan dengan Hukum (International Forum of Researchers and Lecturers, 2025)
Children in conflict with the law (ABH) are part of a vulnerable group that requires a special legal approach and social protection. The development of the concept of the juvenile criminal justice system in Indonesia has undergone a significant transformation since the enactment of Law No. 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA). This law emphasizes the importance of a restorative justice approach and the resolution of juvenile cases from the formal justice system to a more humane and rehabilitative form. The Correctional Center (BAPAS) as an institution tasked with carrying out guidance and supervision of correctional clients including children, plays a central role in this process. Starting from the pre-adjudication, adjudication, to post-adjudication stages, BAPAS is responsible for ensuring that children's rights are protected and children receive guidance in accordance with the principle of the best interest of the child. However, in practice, there are still many challenges in implementing the role of BAPAS. Starting from limited resources, lack of coordination between institutions, to delays in the preparation of community service and child assistance. Therefore, it is necessary to review the effectiveness and challenges in implementing the BAPAS function within the framework of child rehabilitation and reintegration.